The Problematics of Regulating the Maximum Duration of Fixed-Term Employment Agreements Based on the Completion of Specific Work in Legislation: An Analysis of the Implications of Constitutional Court Decision Number 168/PUU-XXI/2023 - I Wayan Agus Mahendra; I Nyoman Bagiastra (Transpublika Publisher, 2025)
The purpose of this study is to discuss the problematic of setting the maximum term limit for a Fixed-Term Employment Agreement (PKWT) based on the completion of a certain job in the legislation, and to allow the implementation of the Constitutional Court (MK) Decision Number 168/PUU-XXI/2023. This Constitutional Court Decision stipulates that the maximum term of PKWT is 5 years, including extensions, which aims to protect workers' rights. This study explores the legal impact of the decision on the implementation of PKWT in Indonesia, including its impact on the provisions of the Job Creation Law and Government Regulation (PP) Number 35 of 2021. The implications of this decision lead to the need to revise provisions that conflict with the Constitutional Court's decision, as well as the need to draft a new law separate from the Job Creation Law to align employment policies with constitutional principles.